PENINGKATAN PEMAHAMAN MATEMATIS DAN KEMAMPUAN KOLABORASI SISWA SEKOLAH DASAR MELALUI SELF PROGRESS LEARNING - Rofikasari, Ingka; Anas Thohir, M; Fithriyanasari, Elly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve second-grade elementary school students’ mathematical understanding and collaboration skills through the implementation of Self-Progress Learning (SPL). The method used in this study is Classroom Action Research (CAR) based on Kurt Lewin’s model, which consists of four stages—planning, action, observation, and reflection—carried out in a cycle. The study was conducted in the second grade at SDN Kauman 1 during the even semester of the 2026/2027 academic year. The background of this study was the low level of students’ mathematical understanding and collaboration skills, caused by variations in students’ learning speeds when grasping mathematical concepts. The learning strategies used were not yet able to accommodate these variations, thereby potentially hindering the development of students’ potential. The research subjects consisted of 29 students with diverse academic abilities. The study was conducted over two cycles, with each cycle comprising two teaching sessions. The selection of research subjects was based on initial observations and interviews with the classroom teacher, which indicated that students’ mathematical understanding and collaboration skills were still relatively low. The results of the study indicate that the implementation of SPL can significantly improve students’ mathematical understanding and collaboration skills. The improvement in mathematical understanding is evident from the students’ average academic scores, which increased from 65 in the first cycle to 88 in the second cycle.